Stress study on natural gas piping system using computer aided engineering simulator - Yaacob, Zulkefli (Penerbit UTM Press, 2008)
Natural gas is transported to customer via gas pipeline. Any damage in the piping system will bring difficulties and even danger to public as well as the appropriate company. Therefore, the purpose of this study is to carry out stress analysis and displacement magnitude of natural gas piping system at Gas System Laboratory of University Technology Malaysia, as well as the capability of the supports to hold the whole piping system once it operated. In addition, modification of pipe supports location will be discovered in this study too. This study will focus on the stresses for natural gas piping system at Gas System Laboratory of UTM only and the piping system is designed by Gas Piping Design Group of Faculty of Chemical and Natural Resources (FKKKSA), UTM. In order to conduct this project, a Computer Aided Engineering Simulator will be used throughout this study. Only sustained loads and thermal expansion are considered in this study. The simulation results show the sum of these factors is 181.76 MPa where it is less than the allowables (241.3MPa). This performs that the design piping system is well-restrained. Modification of the supports location is done to reduce the stresses that act on the piping system. The result shows the sum of sustained loads and thermal expansion is reduced to 181.75 MPa. In conclusion, the pipe stress analysis software proposed is able to compute the stress for the piping system in this study. In addition, modification of the supports location can be considered to ensure the system is adequate for public safety once it operates.